Mrs. pierce is praying for me eaudiobook - Etchison, Dennis (Twilight Zone Radio Dramas., 2013)
A small time hustler who's down on his luck and running from the mob seeks the help of an old woman, Mrs. Pierce, to help him save his older brother's life.